Simulation-based Training for Pelvic and Breast Physical Examination: Effect on the Anxiety and Self-confidence of Medical Students - Talles Dias Orsi; Ana Lucia Ribeiro Valadares; Paula Miranda Esteves Orsi; Isabella Miranda Esteves Orsi; Alexandre Sampaio Moura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective: To evaluate factors associated with anxiety and the effect of simulation-based training (SBT) on student anxiety, self-confidence and learning satisfaction in relation to pelvic and breast examination. Methods: A longitudinal study was conducted with 4th year medical students at the Universidade José do Rosário Vellano. A 12-item, self-report questionnaire on student anxiety at performing gynecological examinations was applied before and after SBT, with answers being given on a Likert-type scale. After training, the self-confidence levels and satisfaction of the students related to the learning process were also evaluated. Results: Eighty students with a mean age of 24.1 ± 4.2 years were included in the study. Of these, 62.5% were women. Pre-SBT evaluation showed that students were more anxious at performing a pelvic examination than a breast examination (2.4 ± 1.0 versus 1.7 ± 0.8, respectively; p < 0.001). The primary reason for anxiety regarding both pelvic and breast examination was fear of hurting the patient. SBT significantly reduced student anxiety (2.0 ± 0.8 versus 1.5 ± 0.5, respectively; p < 0.001). The satisfaction and self-confidence of the students were found to be high (6.8 ± 0.3 and 6.0 ± 0.9, respectively), with no difference between genders. Conclusion: The use of SBT in teaching students to perform pelvic and breast examinations resulted in reduced anxiety and increased self-confidence in a group of medical students of both genders, with high levels of satisfaction in relation to the training.